P-029. Evaluation of 24-year followig results of patients with inactive hepatitis B - Altas, Irem (Turk J Gastroenterol, 2019)
INTRODUCTION: In this study, we aimed to evaluate the long term prognosis and real life data of patients with HBsAg positivity and inactive carriers. METHODS: Inactive hepatitis B carrier 1147 patients whom are under follow-up of out-patient chronic hepatitis clinic of Health Science University, Izmir Bozyaka Training and Research Hospital Infectious Diseases Unit from 1994–2018 were included in the study. The patients files were analysed for socio-demographical information, signs of disease and laboratory findings at the begining and during the follow-up period and all data were collected and recorded to Excell programme. As a second step, patients that did not attend to control examinations for more than one year were called and a questionnaire form were filled by either on phone calls or face to face interwievs. FINDINGS: Of 1147 patients, 50.5% were men and the mean age was 50,17±12. When current statuses of 1147 patients were evaluated: 73% were still inactive carriers, 2% were under anti-viral treatment, 11% had acute inflammation of the disease, 13.6% had spontaneous HBsAg clearence (16.2 per 1000 patient years) and 0.5% had cirrhosis and/or hepatocellular carcinoma. When coherence to control visits were evaluted,60% of inactive carriers were not attending regularly to controls and only 6.5% attended to control visits after they were called. Among patients with acute inflammation of the disease, 53% were not attending regularly to controls and only 4% attended to control visits after they were called. Among patients that were under anti-viral treatment, 63,6% were still attending to controls. When HBV-DNA situations were evaluated: In 15% inactive carriers, in 91% of patients that are under anti-viral treatment, in 72% of patients with acute inflammation and 6% of patients with spontaneous HBsAg clearence HBV-DNA levels reached to ≥104 copy/ml or≥2000 IU/ml at least for once during the follow-up period. When results of abdominal ultrasonographies at the begining and at the last patient visit were evaluated: In two patients (%0,2) a mass lesion of the liver and in one patient (0.1%) a cirrhotic pattern was developed. Presence of hepatosteosis reached from 20% to 25%, hepatomegaly reached to 2% to 6% and splenomegaly reached to 0.8% to 1.1%. CONCLUSION: As long term prognosis of inactive HBsAg carriers are not still well known and still few studies exists in the literature, we believe that more studies should be performed comprising long term follow-up results of those patients. The fact that inactive carriers are mostly asymphtomatic, only laboratory tests are performed at their control visits and no medications are introduced for their disease, make them to believe they are not really ill so underestimate their situation. As the risk of HCC and/or cirrhosis still does exist, acute inflammations and so a need for anti-viral treatment may appear in years, emphasizing the importance of treatment compliance to those pateints is important.